Treatment of space loss caused by submerged maxillary second primary molar - Karacay S; Guven G; Basak F (Wolters Kluwer Medknow Publications, 2007)
Submersion is a clinical term describing a tooth depressed below the occlusal plane. In this case report, we present the treatment of a patient who had totally submerged primary maxillary second molar, which caused impaction of the second premolar and space loss in the maxillary arch due to tipping of adjacent teeth. A 12-year-old girl was referred to the pediatric dentistry clinic. The intra-oral examination revealed that right maxillary second primary molar was localized buccal side of posterior maxillary alveolar process, being almost completely covered by gingiva and adjacent teeth inclined closing the space of the related teeth completely. Periapical radiograph demonstrated that maxillary second premolar was impacted. Based on clinical and radiographic findings, maxillary primary second molar was extracted. Headgear was used for the distalization of maxillary right first molar in order to create space for the impacted second premolar. Eruption begun spontaneously 6 months later.